Resistência de clones de cajueiro à mosca-branca-do-cajueiro Aleurodicus cocois (CURTIS, 1846) (Hemiptera: Aleyrodidae) e aspectos biológicos do inseto - Santos, Elaine Silva do (2016)
The culture of the cashew tree, Anacardium occidentale L. is one of the most important sources of employment and income in Northeast Brazil. Among the main problems that reduce the potential of this culture is the cashew whitefly, Aleurodicus cocois (Curtis, 1846) (Hemiptera: Aleyrodidae), which is spread by all producing regions in Brazil. To minimize the impact of this pest have been used interchangeably chemicals, which increases the risk of development of resistant populations. Thus it is clear the need for research to seek the development of control methods that provide a practical and safe solution. Thus, the objective was to study the biological aspects of A. cocois and resistance of dwarf cashew clones forward to his attack. The average duration of the biological cycle (egg-adult) of cashew whitefly in clone CCP 76, was 33.1 days and the plague takes around six months to reach the maximum level of infestation, colonizing the entire sheet. The resistance was evaluated in field conditions (experimental field in Pacajus-CE) for 25 clones and in laboratory conditions for CCP 76 clones BRS 226, EMBRAPA 51, BRS 274 and PRO 143/7. There were no statistically significant differences between clones, as the infestation of cashew whitefly tree in the field. In the laboratory, the clone PRO 143/7 stood out to attract a smaller number of adults, compared to the other clones, in addition to being less oviposited, the test no choice. In the evaluation of oviposition under free choice, the CCP 76 clone was the most preferred. To characterize the morphological and chemical resistance of the clones, there was the quantification of trichomes, cuticular striations between stomata, leaf thickness, epidermal thickness in both leaf surfaces in scanning electron microscopy, as well as histochemical detection of total phenolic compounds of cashew leaf by means of optical microscopy and confocal. There was a negative correlation between the number of trichomes and number of eggs, revealing that the glandular trichomes negative influence on oviposition of A. cocois. The PRO 143/7 clone stood out for presenting the highest average number of glandular trichomes on the abaxial face and strong detection of phenolic compounds in both studies with microscopy, again indicating this clone can possess the A. cocois resistance factors.